Commodity risk assessment of Albizia julibrissin plants from Israel. (13th January 2020) - ,; Bragard, Claude; Dehnen‐Schmutz, Katharina; Di Serio, Francesco; Gonthier, Paolo; Jacques, Marie‐Agnès; Jaques Miret, Josep Anton; Justesen, Annemarie Fejer; MacLeod, Alan; Magnusson, Christer Sven; Milonas, Panagiotis; Navas‐Cortes, Juan A; et al.
Abstract: The EFSA Panel on Plant Health was requested to prepare and deliver risk assessments for commodities listed in the relevant Implementing Acts as 'High risk plants, plant products and other objects' [Commission Implementing Regulation (EU) 2018/2019 establishing a provisional list of high‐risk plants, plant products or other objects, within the meaning of Article 42 of Regulation (EU) 2016/2031]. The current Scientific Opinion covers all plant health risks posed by Albizia julibrissin imported from Israel, taking into account the available scientific information, including the technical information provided by Israel. The relevance of an EU‐regulated pest for this opinion was based on evidence that: (i) the pest is present in Israel; (ii) A. julibrissin is a host of the pest and (iii) the pest can be associated with the commodity. The relevance of this opinion for other non EU‐regulated pests was based on evidence that (i) the pest is present in Israel; (ii) the pest is absent in the EU; (iii) A. julibrissin is a host of the pest; (iv) the pest can be associated with the commodity and (v) the pest may have an impact and can pose a potential risk for the EU territory. Three pests (two insects, Aonidiella orientalis and Euwallacea fornicatus ; one fungus, Fusarium euwallaceae ) that fulfilled all criteria were selected for further evaluation. For the three selected pests, the risk mitigation measures proposed in the technical dossier were evaluated. Limiting factors on the effectiveness of the measures were documented. For the selected pests, an expert judgement on the likelihood of pest freedom is given taking into consideration the risk mitigation measures acting on the pest, including uncertainties associated with the assessment. The Panel is 95% sure that 9, 950 or more units per 10, 000 will be pest free from these three pests.